(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The article argues that the Mexican leader and politician, Vicente Lombardo Toledano, who dedicated his life to the creation of labor unions, newspapers, workers’ universities, magazines and parties, held a concept of popular democracy whose axis and executor was the State. he methodological focus to elaborate the arguments of this article is not only social and political history but also the biography with which it is articulated. he articulation of history and biography grants a subjective dimension to the projection of the individual in the trajectory of his times. he article is based primarily on the archive of Lombardo Toledano and combines information from this archive with other archives, permitting one to reexamine the relations between Lombardo Toledano and the Mexican Communist Party, the compromises between him and Fidel Velázquez and the methods to achieve the ctm’s penetration in the country’s states. Ultimately, the problem that the article discusses is worker’s democracy and union autonomy.